Cyclic fatigue life of Tango-Endo, WaveOne GOLD, and Reciproc NiTi instruments - Koray Yılmaz; Taha Özyürek (Korean Academy of Conservative Dentistry, 2017)
Objectives To compare the fatigue life of Tango-Endo, WaveOne GOLD, and Reciproc NiTi instruments under static model via artificial canals with different angles of curvature. Materials and Methods Reciproc R25, WaveOne GOLD Primary, and Tango-Endo instruments were included in this study (n = 20). All the instruments were rotated in artificial canals which were made of stainless steel with an inner diameter of 1.5 mm, 45°, 60°, and 90° angles of curvatures and a radius of curvature of 5 mm until fracture occurred, and the time to fracture was recorded in seconds using a digital chronometer. The data were analyzed using Kruskal-Wallis and post-hoc Dunn tests were used for the statistical analysis of data in SPSS 21.0 software. Results Tango-Endo files were found to have significantly higher values than WaveOne GOLD and Reciproc files in terms of fatigue life (p < 0.05). However, there was no statistically significant difference between fatigue life of Reciproc and WaveOne GOLD files (p > 0.05). It was determined that increasing the angle of curvature of the stainless canals caused significant decreases in fatigue life of all of three files (p < 0.05). Conclusions Within the limitations of the present study, the cyclic fatigue life of Tango-Endo in canals having different angles of curvature was statistically higher than Reciproc and WaveOne GOLD.